Biodiversity of herbaceous vegetaton in abandoned and managed sites under protecton regime: a case study in the Central Forest Reserve, NW Russia - Cherednichenko, Oxana; Borodulina, Valentina (Hacquetia, 2018)
The aim of the study is to characterise herbaceous vegetation (meadows and ruderal communities) remaining after several decades of protection and compare it to the vegetation of currently managed local sites in the Central Forest Reserve, Tver Oblast, Russia. Cluster analysis of the communities was based on 209 relevés, while their ecological features were analysed using phytoindication assessment. Te analyses revealed four types of herbaceous communities: managed mesic meadows, abandoned mesic meadows, tall-herb meadowsweet communities and ruderal tall-herb communities. Tese four types diﬀer in management, ﬂoristic composition and ecological conditions as well as in coenotic and functional group shares (including forbs, graminoids and woody species). The occurrence of these species groups determines the current state of the herbaceous communities. Our study revealed that mesic meadows have retained all the key meadow features for more than 25 years without any management, although their area has shrunk and shares of coenotic and functional groups have changed. The observed herbaceous communities encompass around 40% of the reserve ﬂora including four red list species and 16 alien species.